Pengaruh Strategi Integrated Marketing Communication Dan Peran Brand Ambassador Terhadap Brand Awareness Di Masa Pandemi Covid’19 Pada UD. Banana Lava Dan Frozen Food Banyuwangi - Ni’matul Magfiroh; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This Study Aims To Examine And Explain The Effect Of Strategy Integrated Marketing Commnucation And The Role Of Brand Ambassador On Brand Awareness During The Pandemic Covid’19 At UD. Banana Lava And Frozen Food Banyuwangi. This Research Is An Associative Type With A Quantitative Approach. The Method Used Is Multiple Linear Regression. The Sampling Technique Of This Reseach Is Using Purposive Sampling Tehnique Used The Formula From Ferdinan With The Calculation Results Of 65 Samples. To Solve The Problem In This Study Using SPSS Assistance With Validity Test, Reliability Test, Normality Test, Multiple Linear Regression Analysis, Multicollinearity Test, Heteroscedasticity Test, F Test, And T Test. The Results Showed That Simultaneously The Variables Of Integrated Marketing Communication And Brand Ambassador Significant Positive Effect On Brand Awareness. And There Is A Partial Influence Between The Variables Of Integrated Marketing Communication And Brand Ambassador For Brand Awareness. Keywords : Integrated Marketing Communication,Brand Ambassador,Brand Awareness